Integration of Educational Evaluation and Student Character Building in Family Resilience in Makassar City, South Sulawesi - Suriyani, Suriyani; Ilyas, Ilyas (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2025)
This article explores the integration of educational evaluation and its role in character development, particularly in relation to strengthening family resilience. The central question addressed is how educational evaluation contributes to character building within the context of the family. Employing a qualitative research design, this study utilizes a case study approach, with data collected through in-depth interviews and document analysis. Participants included parents, teachers, and educational leaders in South Sulawesi, Indonesia. The findings indicate that educational evaluation plays a dual role: for students, it serves as a tool to recognize their individual capacities and social positioning within the classroom; for educators, it provides insight into the effectiveness of their pedagogical strategies. Education is identified as a key instrument in character formation, shaping individuals with intellectual depth, moral integrity, physical vitality, and a strong sense of self. Among various influencing factors, education emerges as the most impactful in character development. In the context of Makassar City schools, teacher-led evaluations that incorporate character education into family settings have proven effective in supporting parents in guiding their children away from negative social influences